Effect of Curvularia andropogonis Fungus Infection on Epidermal Tissue Anatomy of Citronella Leaves (Cymbopogon nardus (L.) Rendle) - Solekha, Rofiatun; Halma, emil Milhatul Maflahah; Ramadani, Aisyah Hadi; A’in, Nur Khurotul (BEST Journal (Biology Education, Sains and Technology), 2023)
Curvularia andropogonis is a plant pathogenic fungus that causes red spot disease on citronella leaves it infects. This fungus can cause long splotches along the tips and edges of leaves which can result in damage to the entire leaf. In citronella plants, anatomical analysis is needed in the form of analysis of the value of the number and density of stomata and trichomes. Stomata are one of the structural defenses for plants against environmental stresses such as pathogenic infections. In addition to stomata, trichomes also contribute to plant defense and have a protective function. This study aims to analyze the influence of C. andropogonis fungal infection on changes in the anatomy of the epidermal tissue of citronella leaves and to determine differences in the density of stomata and trichomes in normal citronella leaves and citronella leaves infected with C. andropogonis fungus. This research method uses analysis of the number and density of stomata and trichomes using paired t test. The results showed that the average stomata density of healthy citronella leaves was ±470 stomata/mm2 and after being infected, the average density was ±312 stomata/mm2. The average density of healthy citronella leaf trichomes was ±267 trichomes/mm2 and after infection the average density was ±222 trichomes/mm2.